Indian Diaspora and Cultural Pluralism. - Padmaja, C. V. (IUP Journal of English Studies, 2015)
Edward B Taylor observes, "Culture is that complex whole which includes knowledge, beliefs, art, morals, laws, customs and any other capabilities and habits acquired by man as a member of society" (Jayaseelam, 1999, p. 12). An Indian immigrant who migrates to different countries of the world has to encounter with different cultures; these cultures made India a country of pluralism. Nevertheless, plurality in Indian society is not the result of people moving into India, for India already had intrinsic plurality. The Hindu way of life with its umpteen philosophical systems and immense linguistic and literary diversities has given an Indian the advantage of being absorbed into any country in the world. The migrant cultures have only given the country a unique cultural enrichment that has been mutual. The paper attempts to show how the cultural pluralism which has spread in our country by different ethnic cultures--Jews, Parsis, Afghans and Turks and many more--has given a cultural advantage to our country.